Effect of cold water immersion on muscle damage indexes after simulated soccer training in young soccer players - Roonkiani Saman Khakpoor; Ebrahimi Mohsen; Majelan Ali Shamsi (Sciendo, 2020)
Study aim: To investigate the effect of cold water immersion (CWI) on muscle damage indexes after simulated soccer activity in young soccer players.